Surfactant screening to generate strong foam with formation water and crude oil - Memon, M.K. (Springer Science and Business Media Deutschland GmbH, 2021)
Most of the available commercial surfactants precipitate due to the hardness of formation water. The study of surfactant generated foam and its stability is very complex due to its multifaceted pattern and common physicochemical properties. This research involved the study of foam generation by using the blended surfactants and their evaluation in terms of enhanced oil recovery (EOR). The objective of this study is to systematic screening of surfactants based on their capability to produce stable foam in the presence of two different categories of crude oil. Surfactant types such as non-ionic, anionic and amphoteric were selected for the experimental study. The foam was generated with crude oil, and the synthetic brine water of 34,107Â ppm used as formation water. Surfactant concentration with the both types of crude oil, foam decay, liquid drainage and foam longevity was investigated by measuring the generated foam volume above the liquid level. The surfactant with concentration of 0.6wtAOSC14-16, 1.2wtAOSC14-16, 0.6wtAOSC14-16 + 0.6wtTX100 and 0.6wtAOSC14-16 + 0.6wtLMDO resulted in the maximum foam longevity with formation water and two categories of crude oil. The 50 liquid drainage and foam decay of surfactant solutions with concentration of 0.6wtAOSC14-16 + 0.6wtLMDO and 0.6wtAOSC14-16 + 0.6wtTX100 were noted with the maximum time. The findings of this research demonstrated that the generated foam and its longevity is dependent on the type of surfactant either individual or blended with their concentration. The blend of surfactant solution combines excellent foam properties. Â© 2021, The Author(s).